Mixed-cropping enhances profitability and reduces greenhouse gas emissions in semi-arid dryland cropping regions - Sadeeka L. Jayasinghe; Dean T. Thomas; Michael Young (Agricultural Systems, 2026)

Assessment of Coconut (Cocos nucifera L) Jaggery Enriched with Selected Spices on Postprandial Blood Glucose Reduction in Healthy Humans - H. P. D. T. Hewa Pathirana; L. L. W. C. Yalegama; W. L. I. Wijesekara; M. A. Jayasinghe; D. L. C. N. Hitigedara (Sugar Tech, 2026)

Apristurus iterum , a new shark discovered based on egg case morphology and sequence data obtained from a formalin‐fixed specimen - William T. White; Helen L. O'Neill; Sahan A. Jayasinghe (Journal of Fish Biology, 2025)
Apristurus iterum , a new species of deepwater catshark, is described from northeastern Australia. The new species is diagnosed through examination of its unique egg case morphology based on a single whole gravid female specimen and 10 egg cases deposited in different Australian ichthyological collections. This discovery prompted a more detailed investigation of Apristurus specimens collected off Queensland, northeastern Australia. The voucher of the gravid female with two egg cases, previously identified as ‘ Apristurus ’, collected off southeast Queensland, was designated as the holotype and used to describe the new species. The egg cases of A. iterum n. sp. differ from other Australian congeners by possessing distinct, weakly T‐shaped, longitudinal ridges on the dorsal and ventral surfaces. A recently developed molecular approach was successfully applied to extract viable genetic material from the formalin‐fixed holotype specimen. The extracted DNA underwent high‐volume next‐generation sequencing, and the resulting data were processed using a targeted mitochondrial genome alignment approach to generate a short, 160‐nucleotide fragment of the cytochrome c oxidase subunit I ( COI ) gene, which was used for maximum likelihood phylogenetic analysis. The phylogenetic relationships and egg case morphology strongly support this species as being most closely related to Apristurus ovicorrugatus from northwestern Australia and Apristurus nakayai from New Caledonia and Papua New Guinea, with these three species representing a new subgroup within the Apristurus brunneus group.

Effects of Harvesting Techniques and Value Addition on the Nutritional and Physicochemical Properties of Coconut (Cocos nucifera L.) Jaggery - H. P. D. T. Hewa Pathirana; L. L. W. C. Yalegama; W. L. I. Wijesekara; M. A. Jayasinghe; D. L. C. N. Hitigedara (Sugar Tech, 2025)

Predictive Modeling of Glycemic Indices of Value-Added Coconut (Cocos nucifera L) Jaggery Enriched with Specific Ingredients - H. P. D. T. Hewa Pathirana; I. Wijesekara; L. L. W. C. Yalegama; M. A. Jayasinghe; K. P. Waidyarathne; C. N. Hitigedera (Sugar Tech, 2025)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Role of proprioception in corrective visually-guided movements: larger movement errors in both arms of a deafferented individual compared to control participants - Shanie A.L. Jayasinghe; Robert L. Sainburg; Fabrice R. Sarlegna (Experimental Brain Research, 2024)

Bayesian evaluation of temporal changes in sensitivity and specificity of three serological tests for multiple circulating strains of rabbit haemorrhagic disease virus - Kandarp K. Patel; Nils Toft; John Kovaliski; Bradley Page; Ridma M.J. Jayasinghe Ellakkala Appuhamilage; Patrick L. Taggart (Preventive Veterinary Medicine, 2024)

Postharvest stem-end browning (SEB) disease in ripe mango (Mangifera indica L.) cultivar TomEJC - N.K.B. Adikaram; S.S.N. Maharachchikumbura; D.M.D. Yakandawala; L.N. Manawadu; D.M.S. Dissanayake; L. Jayasinghe (European Journal of Plant Pathology, 2023)

Evolution of adverse drug reactions reporting systems: paper based to software based - M. T. Madhushika; T. P. Weerarathna; P. L. G. C. Liyanage; S. S. Jayasinghe (European Journal of Clinical Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of design guideline for the baseplate thickness of lattice towers - A. M. L. N. Gunathilaka; C. S. Lewangamage; M. T. R. Jayasinghe (Innovative Infrastructure Solutions, 2021)

Colletotrichum species causing anthracnose disease in A. andraeanum, manifested as spathe rot also in addition to spadix rot and leaf spot. - I. S. Komala Vithanage; D. M. D. Yakandawala; S. S. N. Maharachchikumbura; L. Jayasinghe; N. K. B. Adikaram (European Journal of Plant Pathology, 2021)

Industrial water conservation by water footprint and sustainable development goals: a review - R. R. Weerasooriya; L. P. K. Liyanage; R. H. K. Rathnappriya; W. B. M. A. C. Bandara; T. A. N. T. Perera; M. H. J. P. Gunarathna; G. Y. Jayasinghe (Environment, Development and Sustainability, 2021)

Upwinding and artificial viscosity for robust discontinuous Galerkin schemes of two-phase flow in mass conservation form - Savithru Jayasinghe; David L. Darmofal; Steven R. Allmaras; Eric Dow; Marshall C. Galbraith (Computational Geosciences, 2021)

Adjoint analysis of Buckley-Leverett and two-phase flow equations - Savithru Jayasinghe; David L. Darmofal; Marshall C. Galbraith; Nicholas K. Burgess; Steven R. Allmaras (Computational Geosciences, 2018)

A space-time adaptive method for reservoir flows: formulation and one-dimensional application - Savithru Jayasinghe; David L. Darmofal; Nicholas K. Burgess; Marshall C. Galbraith; Steven R. Allmaras (Computational Geosciences, 2018)

Conversion between solid and beam element solutions of finite element method based on meta-modeling theory: development and application to a ramp tunnel structure - J. A. S. C. Jayasinghe; M. Hori; M. R. Riaz; M. L. L. Wijerathne; T. Ichimura (Earthquake Engineering and Engineering Vibration, 2017)

Screening of fungicides against Corynespora leaf fall disease of rubber under nursery conditions - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2010)

Evaluation of screening methods against Corynespora leaf fall disease of rubber (Hevea brasiliensis) - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; W. P. K. Silva; E. A. D. N. Nishantha (Journal of Plant Diseases and Protection, 2010)

Variability of Hevea isolates of Corynespora cassiicola from Sri Lanka - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2009)

Determining Tissue-Lead Levels in Large Game Mammals Harvested with Lead Bullets: Human Health Concerns - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; E. P. VanSpronsen; E. N. Liberda (Bulletin of Environmental Contamination and Toxicology, 2009)

Lead Pellet Ingestion and Liver-Lead Concentrations in Upland Game Birds from Southern Ontario, Canada - N. Kreager; B. C. Wainman; R. K. Jayasinghe; L. J. S. Tsuji (Archives of Environmental Contamination and Toxicology, 2008)

Dihydrochalcones with radical scavenging properties from the leaves of Syzygium jambos - U. L. B. Jayasinghe; R. M. S. Ratnayake; M. M. W. S. Medawala; Y. Fujimoto (Natural Product Research, 2007)

(2-Nitro ethyl)phenyl and cyanophenyl glycosides from the fruits of Diploclisia glaucescens - U. L. B. Jayasinghe; N. Hara; Y. Fujimoto (Natural Product Research, 2007)

Soil and Plant Lead of Upland Habitat Used Extensively for Recreational Shooting and Game Bird Hunting in Southern Ontario, Canada - J. Holdner; B. Wainman; R. Jayasinghe; E. Van Spronsen; J. D. Karagatzides; E. Nieboer; L. J. S. Tsuji (Bulletin of Environmental Contamination and Toxicology, 2004)

A fungistatic chromene fromAgeratum conyzoides - M. C. M. Iqbal; U. L. B. Jayasinghe; H. M. T. B. Herath; K. B. Wijesekara; Y. Fujimoto (Phytoparasitica, 2004)

Tissue?Bismuth Levels of Game Birds Harvested with Bismuth Shotshell: Policy Implications - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; J. D. Karagatzides; E. Van Spronsen; E. Nieboer (Bulletin of Environmental Contamination and Toxicology, 2004)